Systems Analysis and Design - Rosenblatt, Harry (Cengage Learning, 2014)
Throughout the book, real-world case studies emphasize critical thinking and IT skills in a dynamic, business-related environment. Numerous projects, assignments, and end-of-chapter exercises, accessible only in CourseMate, provide hands-on practice. The new Tenth Edition will help prepare you for success in today's intensely competitive business world. CourseMate includes an integrated e-book, interactive activities and quizzes as well as the brand new Engagement Tracker feature. In addition, CourseMate is the only place to gain access to the SCR case study.